Combined effects of salt-tolerant varieties and improved nutrient management practices on rice yield and profitability under salt-affected soils in the West African Sahel - Ibrahim, Ali; Kabore, J.E.; Kalimuthu, Senthilkumar; Manneh, Baboucarr; Faye, O.N.; Cisse, M.; Saito, Kazuki (Elsevier, 2025)
Context Soil salinity is one of the major constraints to irrigated rice production in the Senegal River Valley. Several technologies such as salt-tolerant varieties and improved nutrient management practices have been evaluated. However, their on-farm performance is not well known. Objective The objective of this study was to assess the agronomic and economic performance of integrated salinity management options using new rice salt-tolerant varieties. Methods A series of experiments was conducted in both research station and farmers’ fields in dry and wet seasons over two years (2020–2021) in the Senegal River Valley. Seven treatments including T1: recommended practices (Sahel 108, broadcasting, and nitrogen (N) and phosphorus (P) fertilizers); T2: T1 + potassium (K) fertilizer; T3: T2 + gypsum + zinc (Zn); T4: NPK with salt-tolerant rice variety (ISRIZ 10), T5: T4 + gypsum + Zn, T6: NPK with salt-tolerant rice variety (Sahel 108-Saltol), and T7: T6 + gypsum + Zn were evaluated in on-station trials in saline soils with EC value ˃ 4 dS/m. For on-farm trials, each participating farmer selected one from the combination of salinity management options in each season. These options were compared with the recommended practice (Sahel 108 with NP fertilizers) in a total of 170 trials. Results In on-station trials, integrated management options T2, T3, T4, T5, T6 and T7 outyielded T1 by an average 0.8 (23 %), 1.3 (38 %), 1.0 (29 %), 1.9 (55 %), 1.0 (28 %), and 1.9 t/ha (56 %), respectively. Farmers' access to inputs significantly influences their selection of options, and they tended to select the options having inputs that can be easier to access based on their experience. Salt-tolerant rice varieties were used in 85 % of trials. The most common combination of fertilizers selected by farmers was NPK (43 % of fields), followed by NPK + gypsum + Zn (28 %), NPK + gypsum (25 %), and NPK + Zn (4 %). On average, the nutrient management only and integrated salinity management options increased rice yield by 0.9 (24 %) and 1.2 t/ha (26 %), respectively with profitability gain by 258 and 317 (€/ha). Implications Whereas the use of new salt-tolerant varieties together with K and gypsum and/or Zn in salt-affected soils can improve rice productivity and profitability, high costs of these fertilizers and their accessibility remain challenges and improving farmers' adoption of these inputs requires policy and/or market interventions